Struktur dan Fungsi Sastra Lisan KP Nelayan Desa Muara Binuangen - Elih Solihatulmilah; Ira Arini; Hadi Sutiawan; Nandang Faturohman; Anggi Rahmani (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This research is basically behind the emergence of the idea to document the oral literature of the Kp. Fishermen in Muara Village, Wanasama Binuangen District. The general problem of this research is the structure and function of the oral literature of the Kp. Fishermen in Muara Village, Wanasalam Binuangen District. There are three titles analyzed, namely Karang Malang Beach, Makom Nyi Subang Larang Site and Syeh Mansyur Corner. The purpose of this study is to describe the problems discussed, while the benefits of this research are expected to contribute to the development of oral literature research, especially folklore, can be used as teaching materials in schools, can be used as a reference for further researchers, and as an effort cultural preservation, especially Kp. Fishermen in Muara Village, Wanasalam Binuangen District. The theories used in this research are oral literature theory, structural theory, oral literature function, learning system planning, and literary learning. This study uses a descriptive method, the form of this research is qualitative and uses a structural approach and sociology of literature.